2003
DOI: 10.5144/0256-4947.2003.175
|View full text |Cite
|
Sign up to set email alerts
|

Bloody Nipple Discharge in a 4-Year Old Child

Abstract: Breast enlargement is considered a physiologic event in male and female neonates. However, it is rarely encountered in infancy and is deemed unusual in young children beyond the first year of life.1,2 Breast enlargement along with bloody nipple discharge, first reported in 1983 3 appears to be even more uncommon in children. We report a case of a 4-year-old boy with a 2-week history of left breast enlargement with serosanguinous nipple discharge and ipsilateral palpable axillary lymph nodes. Case ReportA 4-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…There are several cases reported in the literature in which biopsy and mastectomy specimens in children and neonates showed the same type of duct ectasia seen in adults. 3,[5][6][7][8] Mammary duct ectasia is a benign process characterized by dilated ducts surrounded by fibrosis and inflammation. 8 Duct ectasia with BND seen in neonates and infants is a self-limiting condition that resolves spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…There are several cases reported in the literature in which biopsy and mastectomy specimens in children and neonates showed the same type of duct ectasia seen in adults. 3,[5][6][7][8] Mammary duct ectasia is a benign process characterized by dilated ducts surrounded by fibrosis and inflammation. 8 Duct ectasia with BND seen in neonates and infants is a self-limiting condition that resolves spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…BND in infancy was first reported by Berkowitz et al in 1983 and a few case have been reported so far. In the early cases, subcutaneous mastectomy was generally performed in patients with BND and histological diagnosis was mammary duct ectasia (1)(2)(3)(4)(5)(6). Although these patients were over-treated with surgery, histological examinations highlighted their benign nature.…”
Section: Discussionmentioning
confidence: 99%
“…These hormones lead to persistence of mammary ducts, which resolve spontaneously after a few weeks or months. This assumption is based on histological results because in most cases mammary duct ectasis was identifi ed as the underlying alteration [1,4,15,17,25,33] . The authors suggest that widened mammary ducts lead to a bleeding from ulcers within the ducts.…”
Section: Discussionmentioning
confidence: 99%